2014
DOI: 10.3998/ark.5550190.p008.682
|View full text |Cite
|
Sign up to set email alerts
|

Copper-catalyzed, oxidative sp2 C-H cyanation: facile synthesis of aromatic carbonitriles

Abstract: Cu(OAc) 2 -catalyzed regioselective oxidative C-H cyanation of two different types of aromatics was described, providing facile access to functionalized heterocycles in good yields. Control experiments suggest the copper chelation-assisted oxidative C-H activation mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Both 2-(naphthalen-2-yl)pyridine 72,73 (9) and 2-(biphenyl-4-yl)pyridine 74,75 (14) could be obtained in excellent average yields in oil bath: 91% in 5 h (9) and 92% in 3 h (14). Similar tendency can be observed for reactions conducted under microwave irradiation, but in shorter reactions of 1 h: 91% for 9 and 95% for 14.…”
Section: Resultsmentioning
confidence: 99%
“…Both 2-(naphthalen-2-yl)pyridine 72,73 (9) and 2-(biphenyl-4-yl)pyridine 74,75 (14) could be obtained in excellent average yields in oil bath: 91% in 5 h (9) and 92% in 3 h (14). Similar tendency can be observed for reactions conducted under microwave irradiation, but in shorter reactions of 1 h: 91% for 9 and 95% for 14.…”
Section: Resultsmentioning
confidence: 99%
“…The stoichiometric mechanistic studies suggested that macrocycle 1054 underwent aerobic C–H metalation with copper­(II) salt to form a stabilized aryl-Cu­(III) complex 1057 which then reacted with KCN to give nitrile 1162 (Scheme ). Likewise, chelation-assisted oxidative C–H cyanation of the (hetero)­arenes has also been accomplished using CuCN as the cyano source …”
Section: Coppermentioning
confidence: 99%
“…Likewise, chelation-assisted oxidative C−H cyanation of the (hetero)arenes has also been accomplished using CuCN as the cyano source. 1632 Capitalizing further on the copper-catalyzed C−H cyanation, Daugulis and Do utilized NaCN for the cyanation of heterocycles such as azoles, imidazoles, and triazoles. 1633 Here, the treatment of heteroarenes with NaCN in the presence of catalytic amounts of CuCN/1,10-phen and with stoichiometric iodine as the oxidant in a mixture of dioxane/xylene gave the cyano-substituted heteroarenes in good yields (Scheme 676).…”
Section: Scheme 505 Pincer Nickel(ii)-catalyzed C−h Bond Alkylation O...mentioning
confidence: 99%
“…Liu also reported the straight Cu-catalyzed regioselective cyanation of 2-arylpyridines and pyrazoles using CuCN as the cyano source in moderate to good yields (Schemes and ) . The addition of KI clearly accelerates the reaction.…”
Section: Metallic Cyano-group Sourcesmentioning
confidence: 99%
“…Liu also reported the straight Cu-catalyzed regioselective cyanation of 2-arylpyridines and pyrazoles using CuCN as the cyano source in moderate to good yields (Schemes 53 and 54). 64 The addition of KI clearly accelerates the reaction. The addition of 10 equiv of AcOH is critical when pyrazole was used as the substrate because it can efficiently inhibit byproducts such as the intermolecular coupling product and the amination product.…”
Section: Cucnmentioning
confidence: 99%